VOCATIONAL TRAINING IN RHYTMIC GYMNASTICS: CENTER OF EXCELLENCE CAIXA YOUTH PLEDGE OF GYMNASTICS (Fiep Bulletin - online, 2013)
The Center of Excellence Caixa Youth Pledge of Gymnastics was created in early 2008, by Brazilian Confederation of Gymnastics, and has the sponsorship of Caixa Econômica Federal. The project covers, initially, fourteen Brazilian states with eighteen Centers of Excellence for the practice of gymnastics. Nine of these centers are of Artistic Gymnastics (male and female) and nine are of Rhythmic Gymnastics (sports only female). The central idea of this initiative is to nurture the sports practice gym, detect young promises in the area, train new technicians in terms of Gymnastics Artistic and Rhythmic Gymnastics and disseminate lessons from a possible "Brazilian School of Gymnastics", based on the good results obtained by country in international events and the importance and necessity of fostering and crowded the practice of gymnastics sports in Brazil. Each of the National Centers of Excellence is able to serve up to 150 children, between five and nine years old. The state of Paraná received two centers, one of Rhythmic Gymnastics, based in Curitiba, another of Artistic Gymnastics, based in Toledo. The article raises the Project for the Center of Excellence Caixa Youth Pledge of Gymnastics as a whole and in particular the process of deployment - installation, organization, progress and prospects - the Center of Excellence Caixa Youth Pledge of Rhythmic Gymnastics of the Federal University of Technology of Paraná (UTFPR), Campus Curitiba. The approach of this work is the issue of training in the area of Rhythmic Gymnastics, given the relationship of the project with the initial training course in Physical stadidaner@uol.com.br 170 Education UTFPR. After their location, through the execution of a search exploratory in nature, it proved the project, apart from a center of education and training of gymnasts, is an area of training and assistance for university teachers and students of Physical Education in diversified areas of knowledge.
Keywords: vocational training; Rhythmic Gymnastics; Physical Education